HiMSC and EV derived treatments increase Quality of Life and reduce amount of Knee Replacement Surgeries compared to current standard of care for knee osteoarthritis patients in The Netherlands - Iris W. A. Boot; Georgina Shaw; Yolande F. M. Ramos; Mary Murphy; Ingrid Meulenbelt; Hubertus J. M. Vrijhoef (PLoS ONE, 2026)
Objectives Current osteoarthritis treatments are designed to reduce pain and improve mobility instead of promoting the regeneration of cartilage. Cell-based therapies are being developed for the treatment of osteoarthritis. The aim of this study was to assess the cost-effectiveness of mesenchymal stromal cells and extracellular vesicle treatments compared to standard of care for patients with Kellgren-Lawrence stage II knee osteoarthritis in the Netherlands, from a hospital and societal perspective. Design A Markov model was developed to assess the 40-year incremental cost-effectiveness ratio of mesenchymal stromal cells and/or extracellular vesicle treatments produced by automated or manual production methods, compared to standard of care. Secondary outcomes were amount of total knee replacement and total knee replacement revision surgeries. In addition, one-way sensitivity analyses and scenario analyses were performed. Results The incremental cost-effectiveness ratios from a hospital perspective were -€10,982.10 for automatically produced mesenchymal stromal cells, -€9,301.79 for manually produced mesenchymal stromal cells, -€12,793.17 for automatically produced mesenchymal stromal cells and extracellular vesicle, and -€11,998.02 for manually produced mesenchymal stromal cells and extracellular vesicle versus standard of care. From the societal perspective incremental cost-effectiveness ratios were €68,870.58 for automatically produced mesenchymal stromal cells, -€67,280.27 for manually produced mesenchymal stromal cells, -€70,771.65 for automatically produced mesenchymal stromal cells and extracellular vesicle, and -€69,976.50 for manually produced mesenchymal stromal cells and extracellular vesicle versus standard of care. The amount of total knee replacement surgeries per 1,000 patients was 426 for the cell treatment groups, and 609 for the standard of care group, and 19 and 30 total knee replacement revision surgeries, respectively. Conclusions This model, inherent to its assumptions, shows that hiMSC and EV treatments are cheaper and more effective for patients with knee osteoarthritis, from both perspectives. Moreover, they are expected to lower the number of surgeries. These conclusions persist among all scenario analyses.